Convergence of Sharia Principles in Otoritas Jasa Keuangan (OJK) Indonesia Regulations and Their Impact on National Financial Policy - Hafizd, Jefik Zulfikar; Arifin, Tajul; Bisri, Hasan; Jubaedah, Dedah (Khazanah Sosial, 2026)
This study analyzes the convergence of Sharia principles within the Financial Services Authority (OJK) regulatory framework and its impact on the transformation of Islamic financing law in Indonesia. Pursuant to Law No. 21 of 2011 on the Financial Services Authority and Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK), OJK is mandated to ensure that all Islamic financial institutions operate in compliance with Sharia principles. However, implementation remains suboptimal, both in terms of regulatory products and practical application. Using a qualitative empirical juridical approach, this study combines normative analysis of statutory regulations, OJK circulars (POJK and SEOJK), and DSN-MUI fatwas with field interviews conducted at the OJK Regional Office in Cirebon. In line with Antonios E. Platsas’s theory of legal convergence, the study finds that OJK’s regulatory approach reflects a multimodal integration of top-down legal harmonization and institutional adaptation of Sharia ethics. Nonetheless, convergence in practice remains largely formalistic, as many regulations still prioritize prudential and administrative compliance over substantive realization of maqāṣid al-sharī‘ah. Strengthening coordination between OJK and the Sharia Supervisory Board (DPS) is therefore essential to align regulatory governance with Sharia’s moral objectives of justice, partnership, and sustainability within Indonesia’s national financial system.